2019
DOI: 10.21203/rs.2.16636/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seed-Biopriming of Durum Wheat with Diazotrophic Plant Browth Promoting Bacteria (PGPB) Enhanced Tolerance to Fusarium Head Blight (FHB) and Salinity Stress

Abstract: Background The use of bioinoculants based on plant growth-promoting bacteria (PGPB) to promote plant growth under biotic and abiotic stresses is in full expansion. To our knowledge much work has not been, thus far, done on seed-biopriming of durum wheat for tolerance to biotic and abiotic stresses. In the present work, we report detailed account of the effectiveness a potent bacterial strain with proven plant growth-promoting ability and antimicrobial activity. The isolate was selected following screening of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This strain was positive for the production of IAA, ACC deaminase, and siderophores and was a phosphate and zinc solubilizer (Pandey and Gupta, 2020). Brahim et al (2022) demonstrated that Bacillus pumilus MA9 and Virgibacillus halodenitrificans MA14 significantly improved wheat germination rate due to secretion of auxin, solubilization of inorganic phosphate, and ACC deaminase activity.…”
Section: Carrot Seed Germination Enhancement Potential In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…This strain was positive for the production of IAA, ACC deaminase, and siderophores and was a phosphate and zinc solubilizer (Pandey and Gupta, 2020). Brahim et al (2022) demonstrated that Bacillus pumilus MA9 and Virgibacillus halodenitrificans MA14 significantly improved wheat germination rate due to secretion of auxin, solubilization of inorganic phosphate, and ACC deaminase activity.…”
Section: Carrot Seed Germination Enhancement Potential In Bacteriamentioning
confidence: 99%
“…Germinating seeds are incessantly exposed to many hazardous factors, including pathogens, resulting in biotic stress (Brahim et al, 2022). The ability to produce siderophores and HCN was demonstrated by 18 and nine out of 33 isolates tested, respectively (Supplementary Table S3).…”
Section: Biocontrol Potential Of Isolatesmentioning
confidence: 99%
“…The rhizosphere chemistry and the development of plant-rhizomicrobiome interactions are still poorly characterised, however, emerging studies have reported that various PGPR species can pre-condition the plants for augmented defence responses against abiotic stresses [ 160 , 161 , 162 , 163 , 164 ]. The molecular mechanisms underlying the rhizobacteria-related defence priming show that this induced state suggests a reprogramming in the cellular metabolism and regulatory machinery of the plants.…”
Section: Microbial Biostimulants and Enhancement Of Plant Responses To Abiotic Stressesmentioning
confidence: 99%